An Analysis on the Speech Act of Selena Gomez ”Trust Yourself” in English Speeches YouTube Channel - Nur Fadilah (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2023)
The purpose of this study is to identify the various types of illocutionary act in Selena Gomez's speech